PENYEBARAN TEKNOLOGI KONSERVASI LAHAN KERING MELALUI PEMUKA PENDAPAT DI KABUPATEN BANTUL - Adi, R Kunto (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2007)
The objectives of this research were to know the dissemination of the conservation technology by opinion leaders, extension agent , and mass media. The metods of collecting the primary data has done with interview, with the sum of samples are 60 peoples. The data analysis used by the ANOVA. The results of this research were the dissemination of the conservation technology at high levels, and the roles of opinion leaders which influence to diffution levels of the conservation technology were higher better than extension agent and mass media.